Left brachiocephalic venous occlusion with spontaneous arteriovenous fistula presenting with severe edema in left upper extremity and face: A case report. (April 2023) - Chida, Kohei; Taniguchi, Naoki; Shigemoto, Chika; Ishimine, Tohru; Higashiura, Wataru; Tengan, Toshiho
Abstract: Introduction and importance: The coexistence of central venous occlusion and arteriovenous fistulas (AVF) is rare among non-dialysis patients. Herein, we describe a case of left brachiocephalic venous occlusion with spontaneous AVF, presenting with severe edema in left upper extremity and face. Case presentation: A 90-year-old woman presented to our hospital with gradually worsening edema in her left arm and face for eight years. Contrast-enhanced computed tomography revealed left brachiocephalic venous occlusion and severe edema in her left upper extremity and face. Computed tomography also revealed abundant collateral veins; thus, it seemed unnatural for severe edema to occur with such well-developed collateral pathways. Therefore, the presence of AVF was suspected. After careful re-examination of the patient, a continuous murmur was heard in the post-auricular region. Magnetic resonance imaging and angiogram revealed a dural AVF. Considering the patient's age and treatment difficulty for the dural AVF, we performed a stent insertion into the left brachiocephalic vein. After the procedure, edema in her left upper extremity and face improved dramatically. Clinical discussion: In cases of persistent swelling of the upper extremities or face, there could be a factor that increases venous inflow. Therefore, any condition that may increase venous inflow must be aggressively investigated and therapeutic interventions should be applied to treat such conditions. Conclusion: Central venous occlusion and AVF is a possible underlying cause for severe refractory edema in the upper extremity and face. Therefore, both AVF and brachiocephalic occlusion should be assessed for treatment indications under these conditions. Highlights: Coexistence of central venous occlusion and AVF is rare among non-dialysis patients. AVF leads to venous hypertension in patients with central venous occlusion. Search for conditions that increase venous inflow even in non-dialysis patients Consider applying therapeutic intervention if such conditions are found Careful examination which revealed the dural AVF was the key to diagnosis